Improvement of the fraction of human mercaptalbumin on hemodialysis treatment using hydrogen-dissolved hemodialysis fluid: a prospective observational study. Issue 1 (December 2016) - Maeda, Kenji; Yoshizaki, Shigehito; Iida, Toshiro; Terada, Tomoyoshi; Era, Seiichi; Sakashita, Keiichiro; Arikawa, Hajime
Abstract Background Oxidative stress (OS) is said to increase in hemodialysis therapy, so that the electrolyzed water-hemodialysis (EW-HD) dissolving hydrogen in hemodialysis fluid has been tried for the reduction of OS. It is reported that the risk of cardiovascular disease events increased if the fraction of reduced albumin (human mercaptalbumin (f(HMA))) was low and that the f(HMA) rose at the dialyzer outlet on EW-HD. Therefore, we studied whether the f(HMA) of hemodialysis patients was improved when they received long-term EW-HD treatment. Methods We produced hydrogen-dissolved hemodialysis fluid with EW-C81-HD and carried out EW-HD treatment for 12 patients. The serum albumin redox states of pre- and post-HD were measured in the summer of 2014 (EWHD2014) and in the winter of 2015 (EWHD2015) after 6 months by high-performance liquid chromatography using Shodex-Asahipak ES-502N 7C column. For comparison, 38 conventional hemodialysis (C-HD) patients and 24 healthy subjects were selected. Results The f(HMA) of EWHD2015 significantly increased from EWHD2014 on both pre- and post-HD (pre, 51.32 ± 5.63 % → 58.03 ± 7.43 %; post, 72.04 ± 5.73 % → 76.42 ± 4.67 %). The f(HMA) of C-HD at pre- and post-HD were 51.07 ± 9.07 and 70.53 ± 8.05 %, respectively. The f(HMA) of healthy subjects was 79.11 ± 5.46 %. The f(HMA) of EWHD2014 at pre-HD evidenced no significant difference with that of C-HD at pre-HD, but the f(HMA) of EWHD2015 at pre-HD was significantly higher than that of C-HD at pre-HD. The f(HMA) of C-HD at post-HD was significantly lower than that of both EWHD2015 at post-HD and healthy subjects, but the f(HMA) of EWHD2015 at post-HD showed no significant difference with that of healthy subjects. Conclusions Our data suggest that the f(HMA) may be raised with long-term hemodialysis treatment using hydrogen-dissolved hemodialysis fluid.